Parents’ and Teachers’ Perspectives Regarding Inclusive Curriculum Modifications : Challenges and Strategies for Effective Implementation - Fitria Sari; Dase Erwin Juansah; Ujang Jamaludin (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
Abstract This study aims to explores parents' and teachers' perceptions of curriculum modifications, the factors influencing their acceptance, and the challenges in implementation. This study employed a systematic literature review method adapted from PRISMA framework guidelines relying on literature sources from Scopus and the Watase Uake tool. Thematic analysis was utilized as the interpretive lens within an integrative review framework involving (1) systematic data extraction, (2) thematic coding, and (3) synthesis. The findings of this study indicate that parents focus more on the impact of modifications on their children's social and emotional development, while teachers emphasize academic effectiveness and technical challenges in implementation. Factors influencing their acceptance include school policy support, involvement in decision-making, and professional training for teachers. The main challenges in implementing an inclusive curriculum include ineffective communication between schools and parents, limited resources, and a lack of teacher training. This study recommends increasing parental involvement in curriculum development, strengthening teacher training, and formulating clearer policies. Closer collaboration between schools, teachers, and parents is key to ensuring the successful modification of the curriculum in inclusive schools. Further studies using an empirical approach are suggested to gain a deeper understanding of the effectiveness of curriculum modifications and their impact on students with special needs.